Prominent Kurdish Women: A Historical Islamic Study from the Book "Our Scholars in the Service of Science and Religion" - Abdullah, Dr. Aram Jalal Abdullah (Sulaimani Journal for Humanities, 2026)
The aim of this research is to shed light on the role of some Kurdish women scholars, highlighting their contributions to the scientific and intellectual movement and the fields of knowledge in which they excelled. The research also examines their scientific and intellectual outputs and their impact, as well as identifying their areas of activity in public life and their participation in shaping Islamic civilization. The research is based on the book "Our Scholars in the Service of Knowledge and Religion" by Sheikh Abdul Karim Al-Mudarris, in addition to various historical sources such as biographies, memoirs, and classificatory works.
Keywords: Prominent Kurdish Women; Our Scholars in the Service of Knowledge and Religion book; Role of Kurdish Women; Kurdish Female Scholars; Kurdish Female Writers